Organizational Ecology and Industrial Organization; Old Firms in the Netherlands - Aleid Elizabeth Brouwer (European Regional Science Association (ERSA), 2001)
This paper will be written as a part of my Ph.D. research. Old firms in the Netherlands' which is a research project in the theme of the demography of firms in the research school Systems, Organizations and Management from the University of Groningen, the Netherlands. The demography of firms is relatively new in the Spatial Sciences but nevertheless this is a subject with a long history in other fields of research. The demography of firms is the study of the changes in the population of firms with the use of demographic tools. This field of research can broaden our knowledge of regional-economic dynamics of firms. Other disciplines that investigated this subject are mostly interdisciplinary, using combinations of methods and theories from sociology, economy, demography and geography. In this paper, the focus will not be on the theoretical background of firm demography, but on the dynamics of the survival of firms. This is part of the 'narrow' definition of firm demographics in Economic Geography as mentioned above. This definition includes birth, death, migration and survival in the population of firms. In this paper, the emphasis will be on the exploration of the definition of 'old' in the context of the firm lifecycle. This will be done using a chronological description of Dutch firm activity in the period from the industrial revolution until the present, and by a representation of the location of firm establishments in maps during this period. Furthermore, a list provided by the Dutch Chamber of Commerce of the 500 oldest establishments in the Netherlands at present will be compared with these maps to get more insight in the 'survival rates of firms in the different industrial sectors. One of the difficulties here is the definition of ''old'' in the context of the firm lifecycle. When is a firm old? Is it possible to characterise a firm on the basis of age in years, or can this only be done in relationship to the age of the attributes (products, employees, organisation or establishment) which form the company? To define the firm just by age in years can be problematic because in this way no attention will be given to the stage of development a firm is in. This development of the firm can be seen when one looks at the age of a company according to the product-lifecycle, in which a firm is not mature until it reaches the fourth stage of this cycle. Right now, this last view is less useful, either because practice shows that some firms are in different stages of the product-lifecycle at the same time, some firms stay in the same phase constantly or some firms start their product-cycle in a different phase than the first. Another difficulty is the question of what constitutes a firm. Does the company's name, the product it produces, or the legal status the company has, constitute it as being a firm? The list of the 500 oldest firms used in this paper is based on the age of the settlement. Of course, this is not the most perfect solution for this problem, but it does give an impression of the age and concentration of firms in the Netherlands in the time period from the industrial revolution until the present. Also, the problem with this data is that it does not include data on the firms' migration. In addition, it would be better to compare different lists from different institutions, but at present these data are not available. The goal of analysing this data is to get more insight into the definition of the concepts ''firm'' and ''old'', as used in the Ph.D. research project "Old firms in the Netherlands." A second goal is to get a preliminary idea of how the population of old firms is dispersed over the Netherlands, how the population is divided over the different industrial sectors and how the age pyramid of this population of firms is composed. In this context it is important to know how the division of the firms was during the Industrial Revolution in the Netherlands and whether or not the current situation is comparable. This last comparison will provide an insight into the different rates of survival of firms in the different industrial sectors.
Keywords: 330